Laser-assisted Selective Activation of Injection Molded Chip Packaging Devices with Thermoset Substrate Materials for Intelligent Connectivity Systems in Automobiles - Kordaß, Timo; Bachy, Bassim; Weisser, Mathias; Franke, Jörg (Procedia CIRP, 2017)
The development of sensors, such as in the automotive sector is characterized by increasing miniaturization and variety. Higher integration of functions in electrical and mechanical applications is therefore a logical consequence for further development. In this connection especially technologies can persuade, enabling high design flexibility, combination of electrical and mechanical functions and embedding of further applications. Mechatronic integrated devices are a considerable solution combining mechanical and various electrical functions in an entire component together. Specifically, the ability for insert moulding of MEMS sensor chips and the ability to create circuit carrier in nearly any shape with selective traces and laser drilled vias suite for this production method. A particular focus is on the durability of very fine conductor tracks. With increasing miniaturization especially in high temperature and high voltage applications the typical thermoplastic based substrate materials with their thin chemical plated circuits, reach boundaries in the thermal and mechanical properties. The use of thermoset materials provides a new suitable alternative in this field. The cross-linked, molecular structured thermosets obtain high temperature resistance, combined with high dimensional stability. The thermal expansion is comparative low. With appropriate selection of compound fillers, aligned laser activation parameters and suitable circuit plating system a reliable CTE composition of all materials can be achieved. Thermosetting plastic compounds with laser-activatable additives are indeed in focus of current researches. However, laser-based method for the selective activation of thermosets is currently not available on the market. As a result, it is investigated into alternative laser assisted activation methods which do not require special additives in the substrate compound for electro chemical potential. Instead an assimilated chemical palladium activation is utilized subsequently. Of particular importance is distinct and selective activation with suitable laser parameters, as well as the following electroless chemical copper and additionally galvanic copper plating with appropriate surface quality for electronic surface mount and assembly technologies. Within the article, the research results will be presented, describing the method and giving an insight into the qualified process parameters for the laser and palladium activation, their correlations among themselves as well as the implications onto the following chemical and galvanic plating.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 3D-MID; chemical plating; electronic manufacturing; selective ionogenic and colloidal palladium activation; thermoset substrates